Dampak Efek Pengamat, Sistem Whistleblowing, Asimetri Informasi, dan Tekanan Finansial pada Terjadinya Kecurangan dalam Laporan Keuangan - Dewi, Risma Wati; Hatta, Atika Jauhari; Biyanto, Frasto (Journal of Culture Accounting and Auditing, 2023)
This research was conducted to investigate the impact of the bystander effect, whistleblowing system, information asymmetry, and financial pressure on the condition of financial reports among employees of the Special Region of Yogyakarta Province and Central Java Province. A total of 102 employees were taken as samples using a purposive sampling method, and data collection was carried out through distributing questionnaires. Data analysis uses Multiple Linear Regression Analysis techniques. Research findings show that (1) the bystander effect variable has a significant positive influence on the condition of financial statements; (2) the violation reporting system variable has a significant positive effect on the condition of the financial statements; (3) the information asymmetry variable has a significant influence on the condition of financial statements; (4) The financial pressure variable also has a significant effect on the condition of the financial statements. These results provide an in-depth understanding of the factors that influence the condition of financial reports in the work environment. The implication is that organizations need to strengthen internal reporting systems, reduce information inequality, and manage financial pressures to prevent conditions from occurring. This research contributes to the context of corporate financial security and integrity and can be a basis for the development of more effective anti-fraud policies in the future..